2000
DOI: 10.1007/s004200000162
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium compounds and occupational asthma

Abstract: These three cases, in addition to others reported in the literature, point out an as yet poorly known etiology of occupational asthma to quaternary ammonium compounds in hospital employees. The exact mechanism of the action remains unexplained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 13 publications
(15 reference statements)
4
105
2
4
Order By: Relevance
“…Benzalkonium chloride has bronchoconstrictor properties, being only 7.4 times less potent as a bronchoconstrictor agonist than histamine [28][29][30]. Furthermore, exposure to benzalkonium chloride is a recognised cause of occupational asthma [31][32][33]. The administration of placebo Respimat solution containing benzalkonium chloride in a concentration of 100 mg?mL -1 causes bronchoconstriction with a fall in forced expiratory volume in 1 s (FEV1 ) of o15% from baseline in 4.3% of occasions in patients with COPD [34].…”
Section: Differential Risk With Tiotropium Productsmentioning
confidence: 99%
“…Benzalkonium chloride has bronchoconstrictor properties, being only 7.4 times less potent as a bronchoconstrictor agonist than histamine [28][29][30]. Furthermore, exposure to benzalkonium chloride is a recognised cause of occupational asthma [31][32][33]. The administration of placebo Respimat solution containing benzalkonium chloride in a concentration of 100 mg?mL -1 causes bronchoconstriction with a fall in forced expiratory volume in 1 s (FEV1 ) of o15% from baseline in 4.3% of occasions in patients with COPD [34].…”
Section: Differential Risk With Tiotropium Productsmentioning
confidence: 99%
“…In a recent registry study, the most commonly reported exposure linked to asthma among HCWs were cleaning products, which accounted for 24% of all cases, including 21% of the cases reported among nurses (6). Both general (e.g., bleach, ammonia) and more specific (e.g., quaternary ammonium compounds) cleaning products have been linked to occupational asthma (31). These and other commercial product ingredients, known to be potential respiratory sensitizers and/or irritants, were identified in the walk-throughs conducted for the development of our JEM (Table 4).…”
Section: Univariate Analysis Between Independent Variables As Assessmentioning
confidence: 99%
“…Bezpośrednie toksyczne działanie QACs na nabło-nek oddechowy może więc wynikać z działania enzymów z grupy peptydaz trawiących wydzielone tachykininy, ale także ze zwiększenia ekspresji cząsteczek adhezyjnych na komórkach i nadprodukcji mediatorów zapalnych, takich jak pochodne kwasu arachidonowego (26). Działanie alergizujące QACs, podobnie jak w przypadku innych czynników o małej masie cząstecz-kowej, może wynikać z ich zachowywania się w ustroju jak hapteny, czyli cząstkowe antygeny zdolne do immunizacji po koniugacji z nośnikiem białkowym (27).…”
Section: Mechanizmy Działaniaunclassified